2019 IEEE/ACM 41st International Conference on Software Engineering (ICSE) 2019
DOI: 10.1109/icse.2019.00055
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Approaches for Test Suite Reduction

Abstract: Test suite reduction approaches aim at decreasing software regression testing costs by selecting a representative subset from large-size test suites. Most existing techniques are too expensive for handling modern massive systems and moreover depend on artifacts, such as code coverage metrics or specification models, that are not commonly available at large scale. We present a family of novel very efficient approaches for similaritybased test suite reduction that apply algorithms borrowed from the big data doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…For constructing sets of interesting test cases we will most likely need a multi-objective formulation that combines diversity of sets of values [9] and derivatives/quotients. Practical work on how to select interesting and relevant distance functions for particular purposes and how to speed up distance calculations are also important and recent advances show promise [6].…”
Section: Discussionmentioning
confidence: 99%
“…For constructing sets of interesting test cases we will most likely need a multi-objective formulation that combines diversity of sets of values [9] and derivatives/quotients. Practical work on how to select interesting and relevant distance functions for particular purposes and how to speed up distance calculations are also important and recent advances show promise [6].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies [19], [20] we have shown that test code similarity can provide an effective instrument for test suite prioritization and reduction. Inspired by such studies, in this work we leverage test code similarity for identifying flaky tests.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly to what we did in a previous work [20], we model the tests in T as points in an n-dimensional vector space using the bag-of-words model [42]: each test case t is represented as the multiset (i.e., a set that allows multiple instances of its elements) of the lowercase tokens composing its source code, split by whitespace characters and punctuation. We purposely decided not to manipulate the input data, e.g., we did not exclude comments, as they are exclusively the original ones written by developers and not added by researchers a posteriori, reflecting the real-world nature of our experimental subjects.…”
Section: A: Vector Space Modelingmentioning
confidence: 99%
“…For tracing code coverage, we have used Cobertura, 3 which gives us the ids of the executed code lines for each test case run. Producing coverage information may introduce up to 30% of time overhead during test execution (Cruciani et al 2019). Therefore, the coverage information is produced and collected only for the classes of the system under test, i.e.…”
Section: A Comprehensive Approach For the Automatic Generation And Rementioning
confidence: 99%
“…In Cruciani et al (2019), the authors reduce test suites by computing the similarity among test cases and take the most distant tests as these should be the ones that potentially show faults on several parts of the system. Their reduction approach need not executing tests on the system, hence it performs quickly.…”
Section: Test Suite Reduction Selection and Prioritisationmentioning
confidence: 99%